004 - A Novel Familial Case of Diffuse Leukodystrophy Related to NDUFV1 Compound Heterozygous Mutations (2013)
Introduction: Mitochondrial leukodystrophy due to complex I deficiency is an entity with high genetic heterogeneity, the mutations of the gene NDUFV1 being one of the causes of this disease. It is an autosomal recessive entity that causes a variable phenotype, from a fatal neonatal onset to neurodegenerative disorders in adulthood. Problem Studied: We report 2 siblings, 5 and 2 years of age, with nystagmus, ataxia, impaired consciousness, hemiparesis, hyporeflexia, and psychomotor regression. In brain magnetic resonance imaging, signal abnormalities in large regions of the cerebral white matter were observed, suggesting a demyelinating disease. Materials and Methods: Genomic DNA was obtained from whole blood. The complete coding region of NDUFV1 was amplified in patients and their parents. Each amplicon was purified. Direct sequencing was performed. Intron 6 and exon 7 amplicons from patient 1 were cloned. A skin biopsy was performed in the mother. RNA was isolated. The NDUFV1 complementary DNA (cDNA) was amplified and directly sequenced. In silico analysis was performed. Following diagnosis, treatment with ubiquinol and riboflavin was started. Results: Both patients have the missense mutation c.1156C> T and the 42-base pair deletion in the gene NDUFV1. Bioinformatics analysis indicates that this deletion leads to messenger RNA (mRNA) synthesis with a premature stop codon. Probably, mutant mRNAs were recognized and degraded by the nonsense-mediated mRNA machinery. Analysis of the maternal NDUFV1 cDNA supports this hypothesis. Conclusion: Our results add information on the molecular basis and the phenotypic features of mitochondrial disease caused by NDUFV1 mutations. We can affirm that the mutations are causative of the phenotype. The patients are having a good therapeutic response to the treatment.